HIF-1α had Pivotal Effects on Downregulation of miR-210 Decreasing Viability and Inducing Apoptosis in Hypoxic Chondrocytes - Zhiqiang Chang; Lifeng Huo; Yimin Wu; Pei Zhang (The Scientific World Journal)
Hypoxia-inducible factor 1-alpha (HIF-1α) and some microRNA (miRNAs) play pivotal roles in response to hypoxia-related physiologic and pathophysiologic responses. Up to date, the regulatory mechanisms of these molecules were largely unknown in chondrocytes. In this study, to study the mechanisms of degradation and homeostasis of chondrocytes, the effects of miRNAs and HIF-1α on chondrocytes in physiologic environment were investigated. We found that the overexpression of miR-210 and HIF-1α was present on hypoxia in C28/I2 human chondrocytes significantly by qRT-PCR and western plot. Further study displayed that miR-210 played positive role as a promoter in regulation and its regulated molecules (bcl-xl and PHD-2) in C28/I2 cells on hypoxia by silenced miR-210, silenced HIF-1α, and adding miR-210. Moreover, downregulated miR-210 could significantly repress the viability and increase the apoptosis in C28/I2 cells on hypoxia, compared to those on normoxia. Furthermore, miR-210 could not modulate viability and apoptosis in C28/I2 cells with the HIF-1α knockdown on hypoxia and normoxia. Taken together, this study demonstrated that the MiR-210 was involved in an HIF-1α-dependent way in C28/I2 human chondrocytes for the first time. It also suggested that miR-210 downregulation decreased viability and induced apoptosis in hypoxic chondrocytes depending on HIF-1α.